PHONETIC CHARACTERISTICS OF REGIONAL ENGLISH ACCENTS: A COMPARATIVE STUDY OF RP, COCKNEY AND GENERAL AMERICAN (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article examines the phonetic aspects of three prominent English accents: Received Pronunciation (RP), Cockney, and General American (GA). It provides an overview of each accent's historical and cultural context, followed by a detailed analysis of their key phonetic characteristics.The comparison highlights features such as rhoticity, vowel articulation, and consonant shifts, emphasizing the distinctions and overlaps between these varieties. The dual conclusions underline the linguistic richness and sociocultural significance of regional accents, encouraging readers to appreciate the diversity and evolution of English. This piece is particularly useful for linguists, students of phonetics, and anyone interested in dialectology.